Chrono-analysis: Study applied to a processing unit of swine in Brazil - Coelho, Willian Leonardo Vieira; Matos, Igo de Souza; Gauto, Rubén Francisco; Bueno, Adauto Farias (Zeiki - Revista Interdisciplinar da Unemat Barra do Bugres, 2021)
Continuous improvement methodologies for industrial food processes are critical for keeping competitiveness and offering food with lower costs and appropriate quality. Therefore, this study aims to analyze the operational procedures of deboning and Tuscan sausage sectors in Brazil’s real swine meat industry by employing chrono-analysis tools. The findings show that the production activities of deboning and Tuscan sausage have short lead times, and the average monthly production of the analyzed products is within a range considered regular. There was a possibility of joining some activities developed, equaling the workload, and reducing the workforce. We observed conditions for productivity improvement in both sectors analyzed.